If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.7(3y + 6) = 0 Reorder the terms: 0.7(6 + 3y) = 0 (6 * 0.7 + 3y * 0.7) = 0 (4.2 + 2.1y) = 0 Solving 4.2 + 2.1y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4.2' to each side of the equation. 4.2 + -4.2 + 2.1y = 0 + -4.2 Combine like terms: 4.2 + -4.2 = 0.0 0.0 + 2.1y = 0 + -4.2 2.1y = 0 + -4.2 Combine like terms: 0 + -4.2 = -4.2 2.1y = -4.2 Divide each side by '2.1'. y = -2 Simplifying y = -2
| 1x+3=-7x-25 | | -2(2t+4)=0 | | 8=13-3y-4 | | 11-y=0 | | 3x-4=(x-4) | | 12-y=-6 | | r+0.5r=1650 | | X^2-xk+3x-4=0 | | c+3c+2=5c-1 | | x+0.25x=43 | | 2x-3=5x-3x-3x | | 22.8-9p=8p+2.4 | | 4(2m-5)=28 | | 38700+x-.01x-223939=50000 | | 9k+4.2=k+8 | | -9y+4y-2= | | F-8=-3f | | z-14=-1 | | 22.4-9p=8p+2.4 | | 5x^3+6x^2+3x+14=x+1 | | -3b+2=4b-12 | | z+8=25 | | z+11=28 | | 3x+9-2x= | | 5x+12-4x+3=12 | | 3x-1=6x-4 | | 2^7/6-14=0 | | z+18=28 | | 1000.00/.35 | | x+x+.7x=1 | | 2sec^2t-4=0 | | 3-2(2x-3)+3(1-2x)=8 |